Network Monitoring Sistem Menggunakan Whatsup Gold Pada Pt. Pembangunan Jaya Ancol, Tbk - Siregar, Martua Hami (STIKOM Tunas Bangsa Pematangsiantar, 2021)
PT. Pembangunan Jaya Ancol, Tbk is a company engaged in recreation, resorts and property. This company uses a network system in transaction operations in each of its business units. Often times a problem is found where the disruption of network devices is only discovered after complaints from users, this is very ineffective because besides disrupting company operations it also causes inconvenience to customers which can have a negative impact on the company's image. There is also a problem where IT Support in the unit is not always in place, because it is handling problems at other users' places. And sometimes problems in the unit cannot be resolved immediately, even sometimes something is overlooked. So we need a Network Monitoring System application to monitor the function or failure of network devices from each unit to the datacenter or server, as well as a helpdesk application to speed up problem handling time. With this application the company can monitor the network system at PT. Pembangunan Jaya Ancol, Tbk so that problems occur before complaints from users can be found, and reduce computerized system downtime. And with the helpdesk facility, it makes handling IT problems in users faster to be handled.